PENGARUH MOTIVASI, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DINAS KESEHATAN PROVINSI BALI - Ni Putu Mitha Lestari Dewi; I Nengah Sudja; Yenny Verawati (VALUES, 2022)
Human resource performance or job performance is a person's work performance, thus human resource performance is the quality and quantity of work achieved by an employee based on predetermined standards within a certain time. The purpose of this study was to determine the effect of motivation, work discipline and organizational commitment on employee performance at the Bali Provincial Health Office. The object of research in this research is Motivation, Work Discipline and Organizational Commitment to Employee Performance at the Bali Provincial Health Office. The total population in this study was 150 people. In this study, the sample used was 20% of the total population so that it got 30 respondents. Methods of data collection using a questionnaire. The data analysis technique used multiple linear regression analysis. The results of the study of motivation have a positive and significant effect on employee performance at the Bali Provincial Health Office. Work discipline has a positive and significant effect on employee performance at the Bali Provincial Health Office. Organizational commitment has a positive and significant effect on employee performance at the Bali Provincial Health Office. Work motivation, work discipline and organizational commitment simultaneously have a significant effect on employee performance at the Bali Provincial Health Office.